Malu – fragmentos para preencher lacunas : o processo criativo documental e a prática de si nas artes da cena - Peinado, Daniely (2015)
This research aims to investigate the relationship between memory and creation in Malu – Fragmentos para preencher lacunas, through a continuous, fragmented and flexible dynamic, from the criticism of creative processes (SALLES, 2004, 2006, 2008) and the hermeneutic paradigm (GADAMER, 2010; PALMER, 2006). The starting point for creating is a tragic event: the death of my sister, Marlucia, in May 2014. This fact drives the scenic research into the use of personal memories for artistic representation, promoting the meeting with my story and self reconstruction after the trauma. The path of approachment between life and art, constitutes the poetic construct of the performance, based on documentary theater notions (BASKERVILLE, 2012; GIORDANO, 2013; LEITE, 2012, 2014; SOLER, 2008), performance art (BERNSTEIN, 2001; COHEN, 2006; DIÉGUEZ, 2008; LOPES, 2009) and physical theater (CALLERY, 2001; MALDONADO, 2005; ROMANO, 2005). The study is developed in a qualitative way, combining literature and field research. Facing a procedural and relational thinking, we seek to reveal how are assigned new meanings to life experience (LARROSA, 2002) through artistic experimentation. The narrative of systematization of such procedures is related to the transformation of memory into scene and in academic writing: making plural a single experience, sharing the possibilitie of building knowledge from the experienced. Keywords: Theather; Performance art; Memory; Creative processes Criticism.